Comparing the determinants of concern about terrorism and crime - Tilman Brück; Cathérine Müller (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Both crime and terrorism impose costs onto society through the channels of fear and worry. Identifying and targeting groups which are especially affected by worries might be one way to reduce the total costs of these two types of insecurity. However, compared to the drivers of the fear of crime, the determinants of concerns regarding global terrorism are less well known. Using nationally representative survey data, we analyse and compare the individual determinants of concern about global terrorism and crime, and show that worries about terrorism are driven by similar determinants as those about crime, which could have important policy implications. We furthermore provide an insight into the structure of the determinants of concerns regarding other public and private goods.
Keywords: H40; D01; D81; F52; 330; Terrorism; crime; fear; attitudes; GSOEP; Kriminalität; Politische Gewalt; Angst; Meinung; Vergleich; Deutschland